Alcohol use and drinking patterns in Swedish 85 year olds born three decades apart – findings from the Gothenburg H70 study. (29th March 2023) - Falk Erhag, Hanna; Ahlner, Felicia; Wetterberg, Hanna; Mellqvist Fässberg, Madeleine; Skoog, Ingmar
Abstract: Background: Little is known about alcohol consumption among the oldest old. Objective: To compare alcohol use and drinking patterns among 85 year olds born three decades apart. Design: Cross-sectional. Setting: The Gothenburg H70 Birth Cohort Studies. Subjects: About 1, 160 85 year olds born in 1901–02, 1923–24, and 1930. Methods: Self-reported questions about alcohol included how often study participants drank beer, wine, and spirits and how many centilitres in total/week. Risk consumption was defined as ≥100 g alcohol/week. Descriptive statistics and logistic regression were used to explore cohort characteristics, differences in proportions, factors associated with risk consumption and 3-year mortality. Results: The proportion of at-risk drinkers increased from 4.3 to 14.9% (9.6–24.7% in men and 2.1–9.0% in women). The proportion of abstainers decreased from 27.7 to 12.9%, with the largest decrease observed among women (29.3–14.1%). Controlling for sex, education and marital status, 85 year olds in the later-born cohorts were more likely to be risk consumers than those in the earlier-born cohort [odds ratio (OR) 3.1, 95% confidence nterval (CI) 1.8–5.6]. The only factor associated with an increased likelihood was male sex (OR 3.7, 95% CI 1.0–12.7 and OR 3.2, 95% CI 2.0–5.1). There were no associations between risk consumption of alcohol and 3-year mortality in any of the cohorts. Conclusion: Alcohol consumption and the number of risk consumers among 85 year olds have increased considerably. This could have large public health consequences since older adults are more sensitive to alcohol's adverse health effects. Our findings show the importance of detecting risk drinkers also in the oldest old.